PREDIKSI KELUHAN PELANGGAN PADA APARTEMEN MENGGUNAKAN ALGORITMAC4.5 - Eni Irfiani (Paradigma, 2014)
Customer complaint result in customer dissatisfaction and looses for businesses.  Fierce competition in its property business apartment requires companies to reduce the number of complaints. Therefore, the classifications and predictions technique in data mining is needed to resolve the issue. Classification techniques used in data mining are decision tree.  Decision tree is a technique which is widely use and produce output in the form of rules. The decision tree can present customer complaint pattern behavior. In this study, it uses the algorithm C4.5 to generate classification rules of customer complaints to the apartment and the accuracy result in this study was 75%. Keywords: Customer Complaint, Classification, Prediction, Decision tree, C4.5 Algorithm